Changes in hydro-meteorological conditions over tropical West Africa (1980–2015) and links to global climate - Ndehedehe, C.; Awange, Joseph; Agutu, N.; Okwuashi, O. (Elsevier Science BV, 2018)
© 2018 Elsevier B.V. The role of global sea surface temperature (SST) anomalies in modulating rainfall in the African region has been widely studied and is now less debated. However, their impacts and links to terrestrial water storage (TWS) in general, have not been studied. This study presents the pioneer results of canonical correlation analysis (CCA) of TWS derived from both global reanalysis data (1980–2015) and GRACE (Gravity Recovery and Climate Experiment) (2002–2014) with SST fields. The main issues discussed include, (i) oceanic hot spots that impact on TWS over tropical West Africa (TWA) based on CCA, (ii) long term changes in model and global reanalysis data (soil moisture, TWS, and groundwater) and the influence of climate variability on these hydrological indicators, and (iii) the hydrological characteristics of the Equatorial region of Africa (i.e., the Congo basin) based on GRACE-derived TWS, river discharge, and precipitation. Results of the CCA diagnostics show that El-Niño Southern Oscillation related equatorial Pacific SST fluctuations is a major index of climate variability identified in the main portion of the CCA procedure that indicates a significant association with long term TWS reanalysis data over TWA (r = 0.50, ? < 0.05). Based on Mann-Kendall's statistics, the study found fairly large long term declines (? < 0.05) in TWS and soil moisture (1982 - 2015), mostly over the Congo basin, which coincided with warming of the land surface and the surrounding oceans. Meanwhile, some parts of the Sahel show significant wetting (rainfall, soil moisture, groundwater, and TWS) trends during the same period (1982–2015) and aligns with the ongoing narratives of rainfall recovery in the region. Results of singular spectral analysis and regression confirm that multi-annual changes in the Congo River discharge explained a considerable proportion of variability in GRACE-hydrological signal over the Congo basin (r = 0.86 and R 2 = 0.70, ? < 0.05). Finally, leading orthogonal modes of MERRA and GRACE-TWS over TWA show significant association with global SST anomalies.